The Relationship between Spiritual Well-being and Anxiety Levels in the Students of School of Nursing and Midwifery in Rafsanjan University of Medical Sciences in 2015 - N Rahimi; Z Asadolahi; A Afsharipour (Iran University of Medical Sciences, 2017)
Abstract Background & Aim: In modern societies, anxiety is one of the most common mental health problems. Nowadays, the attention of many religious psychologists has been drawn to the role of spiritual well-being in reducing mental disorders, including anxiety. The present study was designed to investigate the spiritual well-being and anxiety among the students in the School of Nursing and Midwifery at Rafsanjan University of Medical Sciences. Materials & Methods: This research was a cross-sectional and descriptive-analytic study in which 233 nursing, midwifery, and medical students of Rafsanjan University of Medical Sciences participated. The instruments were the Palutzian & Ellison's Spiritual Well-Being Scale and Beck Anxiety Inventory. The obtained data were analyzed in the SPSS-20, using Pearson correlation coefficient and two-sample t-test statistical analysis. Results: The average spiritual well-being of nursing and midwifery students is moderate (98.97 ± 14.7) and their average anxiety was low (24.58 ± 13.7). Moreover, there was a negative correlation between spiritual health and anxiety (r= -0.398). Conclusion: According to the results, it is important to pay attention to spiritual health in nursing, midwifery, and medical emergency students. The spiritual health well-being causes anxiety decrement; thus, to promote spiritual health and reduce anxiety in students, it is necessary to make proper plans.